2013
DOI: 10.1007/s10120-013-0289-z
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study of alternate-day S-1 as adjuvant chemotherapy for gastric cancer: a randomized controlled trial

Abstract: Background The Adjuvant Chemotherapy Trial of S-1 for Gastric Cancer established oral S-1 administration for 1 year as the standard postoperative adjuvant chemotherapy for gastric cancer in Japan. We conducted a multicenter cooperative prospective study comparing daily and alternate-day S-1 administration as postoperative adjuvant therapy for gastric cancer. Methods Patients with Stage II or III gastric cancer who underwent curative surgery were randomly assigned to receive standard daily S-1 administration [g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Another randomized trial investigating feasibility of reduced dose intensity of S-1 comparing full dose as adjuvant chemotherapy for gastric cancer has been reported. Although the study was conducted with a small number of patients, administration of S-1 on alternate days was associated with improvement in compliance, reduction in some adverse events, and no significant difference in overall survival [8]. In recent years, several results of clinical trials have been reported.…”
Section: Discussionmentioning
confidence: 91%
“…Another randomized trial investigating feasibility of reduced dose intensity of S-1 comparing full dose as adjuvant chemotherapy for gastric cancer has been reported. Although the study was conducted with a small number of patients, administration of S-1 on alternate days was associated with improvement in compliance, reduction in some adverse events, and no significant difference in overall survival [8]. In recent years, several results of clinical trials have been reported.…”
Section: Discussionmentioning
confidence: 91%
“…A feasibility study of adjuvant S-1 for gastric cancer had a completion rate of 60.7%, with a high rate of patient refusal due to adverse reactions, especially after the first course (anorexia) [19]. Based on the results of the Adjuvant Chemotherapy Trial of S-1 for Gastric Cancer [8], patients were estimated to refuse S-1 administration even with grade 1 or 2 digestive system adverse events [20]. In a feasibility study of adjuvant S-1 for elderly patients with NSCLC, both the patients and their physicians were speculated to be less willing to tolerate even modest degrees of toxicity, particularly because the benefits of adjuvant chemotherapy were unproven [10].…”
Section: Discussionmentioning
confidence: 99%
“…Our study found a relatively better completion rate over 1 year with the conventional administration schedule than the other studies. Based on the assumption that patients will refuse to continue S-1 with even grade 1 or 2 digestive system adverse events [20], the prophylactic use of lafutidine, a histamine H2 receptor antagonist, to reduce the occurrence of gastrointestinal toxicities might improve patient compliance. There has been a recent report on the efficacy of lafutidine for reducing gastrointestinal toxicity during adjuvant S-1 chemotherapy for patients with gastric cancer [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, many patients who underwent S-1 treatment suffered from drugrelated side effects, including loss of appetite, nausea, and stomatitis. We therefore conducted a randomized trial to investigate the ability of alternate-day S-1 administration to reduce adverse effects and improve the S-1-completion rate [6]. A total of 73 patients were enrolled between November 2005 and October 2009.…”
Section: Patientsmentioning
confidence: 99%
“…The study was conducted in accordance with the Declaration of Helsinki and Good Clinical Practice guidelines. The eligibility criteria and details of the enrolled patients have been described previously [6]. A total of 16 patients were treated at the Tottori University Hospital (university group) and 23 were treated at the Tottori Prefectural Central Hospital (general-hospital group), and these 39 patients were enrolled in this study.…”
Section: Patientsmentioning
confidence: 99%